Rubber foam and laminate

A composition of EPDM, EVA, and nitrogen-based flame retardants in rubber foam addresses the challenge of low density and adhesion issues, ensuring high flame retardancy and strong adhesion to acrylic resin adhesive layers.

JP2025016721AActive Publication Date: 2025-02-04INOAC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024194043
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-04
Estimated Expiration
2040-08-27

AI Technical Summary

Technical Problem

Existing rubber foams using non-halogen-based flame retardants face challenges in achieving low density and high flame retardancy, and those using ethylene-propylene-diene monomer (EPDM) have poor adhesion to adhesive layers containing acrylic resin, leading to potential peeling issues.

Method used

A composition comprising EPDM, ethylene-vinyl acetate (EVA), a foaming agent, crosslinking agent, metal hydroxide, fatty acid ester, and nitrogen-based flame retardants, such as melamine cyanurate, is used to create a rubber foam with high adhesion to acrylic resin adhesive layers while maintaining low density and high flame retardancy.

Benefits of technology

The solution results in a rubber foam with excellent adhesion to acrylic resin adhesive layers and high flame retardancy, achieving low density and passing stringent combustion tests without using halogen-based flame retardants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016721000001_ABST
    Figure 2025016721000001_ABST
Patent Text Reader

Abstract

To provide a rubber foam that does not use a halogen flame retardant but has high flame retardancy, low density, and high adhesion to an adhesive layer containing an acrylic resin.SOLUTION: A rubber foam 1 is a foamed composition containing EPDM, EVA, a foamer, a crosslinker, a metalhydroxide, a fatty acid ester, and a nitrogen flame retardant.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a rubber foam, a laminate, and a method for producing a rubber foam. [Background technology]

[0002] Conventionally, flame-retardant rubber foams have used halogen-based polymers such as chloroprene rubber (CR) and halogen-based flame retardants that have bromine-based halogens in the molecule. Even with a small amount of halogen-based flame retardants, high flame retardancy can be achieved. For this reason, it has been relatively easy to obtain rubber foams with low density and high flame retardancy by using halogen-based flame retardants. For example, Patent Document 1 discloses a rubber foam that uses decabromodiphenyl ether, which is a halogen-based flame retardant, in combination with antimony trioxide. However, rubber foams using such halogen-based flame retardants are likely to emit toxic gases in the event of a fire. In recent years, therefore, there has been a demand for non-halogen flame retardant rubber foams that do not contain halogen flame retardants. It is known that in rubber foams containing non-halogen flame retardants, low density and high flame retardancy are contradictory for the following reasons. That is, if the amount of non-halogen flame retardant is reduced, the rubber foam can be made low-density by blending a small amount of high-density non-halogen flame retardant, but the amount of flame retardant is small and the flame retardancy is low. On the other hand, if the amount of non-halogen flame retardant is increased, the flame retardancy is increased because a large amount of high-density non-halogen flame retardant is blended, but the rubber foam becomes high-density due to the blending of a large amount of high-density non-halogen flame retardant. Therefore, it has been considered difficult to obtain a rubber foam having low density and high flame retardancy using a non-halogen-based filler. Incidentally, when a rubber foam is used as a sealing material, in order to attach and fix it to a vehicle, a panel, or the like, the rubber foam is subjected to an adhesive process in which a pressure-sensitive adhesive layer containing an acrylic resin is formed on the rubber foam. Traditionally, chloroprene rubber has been commonly used as the rubber component in rubber foams used in sealing materials. However, in consideration of recent environmental issues, the use of halogen-free rubber foams as an alternative to chloroprene rubber is being considered. Ethylene-propylene-diene rubber (EPDM) is being considered as the rubber component for such rubber foams. However, rubber foams using EPDM do not have good adhesion (bonding) to pressure-sensitive adhesive layers containing acrylic resins (acrylic polymers), and there is a risk of peeling. Therefore, it is necessary to improve the adhesion of EPDM rubber foam to a pressure-sensitive adhesive layer containing an acrylic resin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-211119 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present disclosure has been made in view of the above circumstances, and has an object to provide a rubber foam having high flame retardancy, low density, and high adhesion to a pressure-sensitive adhesive layer containing an acrylic resin, without using a halogen-based flame retardant.The present disclosure also has an object to provide a laminate having high flame retardancy, low density, and high adhesion between the rubber foam and a pressure-sensitive adhesive layer, without using a halogen-based flame retardant. The present disclosure can be realized in the following forms. [Means for solving the problem]

[0005] [1] A rubber foam, which is a foam of a composition containing EPDM, EVA, a foaming agent, a crosslinking agent, a metal hydroxide, a fatty acid ester, and a nitrogen-based flame retardant. Effect of the Invention

[0006] The rubber foam of the present disclosure has high flame retardancy without using a halogen-based flame retardant, has low density, and has high adhesion to a pressure-sensitive adhesive layer containing an acrylic resin. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a cross-sectional view showing a rubber foam and a laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Here, a preferred example of the present disclosure is given. [2] The rubber foam according to [1], wherein the composition further contains a phosphorus-based flame retardant.

[0009] [3] The nitrogen-based flame retardant is a melamine-based flame retardant, The rubber foam according to [1] or [2], wherein the nitrogen-based flame retardant is present in an amount of 50 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the total of the EPDM and the EVA.

[0010] [4] The water absorption rate measured in accordance with ASTM D 1056 is 0% or more and 30% or less; The rubber foam according to any one of [1] to [3], which has a closed cell structure.

[0011] [5] A laminate comprising the rubber foam according to any one of [1] to [4] and a pressure-sensitive adhesive layer laminated thereon.

[0012] [6] The laminate according to [5], wherein the pressure-sensitive adhesive layer contains an acrylic polymer.

[0013] [7] The laminate according to [5] or [6], wherein the peel strength between the pressure-sensitive adhesive layer and the rubber foam is 5 N / 25 mm or more.

[0014] [8] A method for producing a rubber foam, comprising foaming and crosslinking a composition containing EPDM, EVA, a foaming agent, a crosslinking agent, a metal hydroxide, a fatty acid ester, and a nitrogen-based flame retardant.

[0015] The present disclosure will be described in detail below. In this specification, a description using "~" for a numerical range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".

[0016] 1. Rubber foam 1 Rubber foam 1 is a foam of a composition containing EPDM (ethylene-propylene-diene rubber), EVA (ethylene-vinyl acetate copolymer), a foaming agent, a crosslinking agent, a metal hydroxide, a fatty acid ester, and a nitrogen-based flame retardant.

[0017] (1) Apparent density of rubber foam 1 The apparent density of the rubber foam 1 is set to 0.05 g / cm from the viewpoint of eliminating gaps in the sealing portion and obtaining flexibility to ensure watertightness, airtightness, etc. 3 More than 0.3g / cm 3 Less than 0.06 g / cm is preferred. 3 More than 0.2g / cm 3 Less than 0.07 g / cm is more preferable. 3 More than 0.09g / cm 3 The following is even more preferred: The apparent density of the rubber foam 1 is measured by a measurement method in accordance with JIS K6767.

[0018] (2) Composition The composition contains EPDM (ethylene-propylene-diene rubber), EVA (ethylene-vinyl acetate copolymer), a foaming agent, a crosslinking agent, a metal hydroxide, a fatty acid ester, and a nitrogen-based flame retardant. Each component of the composition will be described.

[0019] (2.1) EPDM EPDM is a rubber obtained by copolymerization of ethylene, propylene, and dienes. EPDM is made possible to vulcanize with a vulcanizing agent by further copolymerizing dienes with an ethylene-propylene copolymer to introduce unsaturated bonds. The dienes are not particularly limited, but non-conjugated dienes are preferred, such as 5-ethylidene-2-norbornene, 1,4-hexadiene, and dicyclopentadiene. From the viewpoint of obtaining the characteristics of the present invention, 5-ethylidene-2-norbornene is preferred as the diene. The content of dienes in EPDM (diene content) is not particularly limited. From the viewpoint of the crosslinking (vulcanization) reaction and the influence of mechanical properties, the content of dienes is preferably 4% by mass or more and 17% by mass or less, more preferably 7% by mass or more and 15% by mass or less. The ethylene content in EPDM is not particularly limited, but from the viewpoints of heat resistance and permanent deformation resistance, the ethylene content is preferably from 40% by mass to 80% by mass, and more preferably from 45% by mass to 60% by mass. The EPDM may be used alone or in combination of two or more kinds.

[0020] (2.2) EVA EVA is flexible and has excellent elongation, and by including EVA in the rubber foam 1, defects such as warping, cracking, and pinfall are suppressed. The melting point of EVA (DSC method) is not particularly limited. The melting point of EVA is preferably 80° C. or more and 90° C. or less from the viewpoint of improving warpage of the rubber foam 1 after molding. The melting point of EVA is measured by the DSC method according to JIS K 7121. The content of vinyl acetate in the EVA is not particularly limited. From the viewpoint of appropriately softening the rubber foam 1 and suppressing defects such as warping, cracking, and pinfall, the content of vinyl acetate is preferably 1% by mass or more, and more preferably 5% by mass or more, when the mass of the EVA is taken as 100% by mass. On the other hand, from the viewpoint of suppressing variations in foaming caused by excessive softening, the content of vinyl acetate is preferably 30% by mass or less, and more preferably 20% by mass or less. From these viewpoints, the content of vinyl acetate is preferably 1% by mass or more and 30% by mass or less, and more preferably 5% by mass or more and 20% by mass or less. The content of vinyl acetate is based on JIS K 6924-2. The blend ratio of EPDM and EVA is not particularly limited. When the total of EPDM and EVA is 100 parts by mass, from the viewpoint of ensuring sufficient peel strength of the rubber foam 1 against the pressure-sensitive adhesive layer 3 and suppressing warpage of the rubber foam 1, the amount of EVA is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. On the other hand, from the viewpoint of suppressing gas escape during foaming and suppressing defects such as pinfall, the amount of EVA is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less. From these viewpoints, the amount of EVA is preferably 5 parts by mass or more and 40 parts by mass or less, more preferably 10 parts by mass or more and 35 parts by mass or less, and even more preferably 15 parts by mass or more and 30 parts by mass or less.

[0021] (2.3) Foaming agent The foaming agent is not particularly limited. Known foaming agents such as organic foaming agents and inorganic foaming agents can be used as the foaming agent. The foaming agent may be used alone or in combination of two or more kinds. As the foaming agent, for example, at least one of dinitropentadienetetramine (DPT), azodicarbonamide (ADCA), 4,4'-oxybisbenzenesulfonylhydrazide (OBSH), and sodium hydrogen carbonate can be used. The amount of the foaming agent is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the foaming agent has a large effect on low density, and from the viewpoint of adjusting the amount of foaming gas to be the rubber foam 1, the amount is preferably 10 parts by mass or more, more preferably 13 parts by mass or more, and even more preferably 15 parts by mass or more. On the other hand, from the viewpoint of ensuring appearance (defects such as cracks and pinfalls), the amount of the foaming agent is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less. From these viewpoints, the amount of the foaming agent is preferably 10 parts by mass or more and 35 parts by mass or less, more preferably 13 parts by mass or more and 30 parts by mass or less, and even more preferably 15 parts by mass or more and 25 parts by mass or less.

[0022] (2.4) Crosslinking agents (vulcanizing agents) The crosslinking agent is not particularly limited. For example, known crosslinking agents such as sulfur, sulfur compounds, selenium, magnesium oxide, peroxide-based crosslinking agents, and p-quinonedioxime-based crosslinking agents can be used. The crosslinking agent may be used alone or in combination of two or more. The amount of the crosslinking agent is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the amount of the crosslinking agent is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more, from the viewpoint of ensuring the physical properties after crosslinking and foam moldability (timing control of foaming and crosslinking). On the other hand, the amount of the crosslinking agent is preferably 3.5 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less, from the viewpoint of bloom resistance. From these viewpoints, the amount of the crosslinking agent is preferably 0.5 parts by mass or more and 3.5 parts by mass or less, more preferably 1.5 parts by mass or more and 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or more and 2.5 parts by mass or less.

[0023] (2.5) Paraffin-based process oil The composition may contain a paraffinic processing oil. The paraffin-based process oil may be a commercially available product, such as Diana Process Oil "PS-430", "PS-32", "PS-90", "PW-32", "PW-90", "PW-150", or "PW-380" manufactured by Idemitsu Kosan Co., Ltd. The amount of the paraffinic process oil is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the paraffinic process oil can ensure the cohesiveness of the compound during kneading and increase the dispersibility of the filler in the clayey compound. From the viewpoint of the kneading processability, the amount is preferably 0 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. On the other hand, the amount of the paraffinic process oil is preferably 80 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, from the viewpoint of suppressing adhesion inhibition due to oil bleeding and ensuring adhesion of the rubber foam 1 to the pressure-sensitive adhesive layer 3. From these viewpoints, the amount of the paraffinic process oil is preferably 0 parts by mass or more and 80 parts by mass or less, more preferably 3 parts by mass or more and 30 parts by mass or less, and even more preferably 5 parts by mass or more and 10 parts by mass or less. A rubber foam containing paraffin-based process oil deteriorates flammability, so the amount of the paraffin-based process oil is preferably as small as possible.

[0024] (2.6) Metal hydroxide The metal hydroxide may be any known metal hydroxide, including at least one selected from the group consisting of aluminum hydroxide, magnesium hydroxide, and calcium aluminate. The amount of the metal hydroxide is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the amount of the metal hydroxide is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, from the viewpoint of ensuring the adhesion of the rubber foam 1 to the pressure-sensitive adhesive layer 3. On the other hand, the amount of the metal hydroxide is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 80 parts by mass or less, from the viewpoint of increasing the dispersibility of the filler. From these viewpoints, the amount of the metal hydroxide is preferably 20 parts by mass or more and 100 parts by mass or less, more preferably 30 parts by mass or more and 90 parts by mass or less, and even more preferably 50 parts by mass or more and 80 parts by mass or less.

[0025] (2.7) Fatty acid esters Fatty acid esters (RCOOR', where R and R' may be the same or different) are both hydrophilic and hydrophobic. It is presumed that the fatty acid ester acts as a surfactant, reducing the aggregation of metal hydroxide and EVA, and acts as a dispersant in the rubber (rubber foam 1). Examples of fatty acid esters include glycerin fatty acid esters, higher alcohol fatty acid esters, sorbitan fatty acid esters, propylene fatty acid esters, and n-butyl stearate. The fatty acid esters may be used alone or in combination of two or more. The fatty acid ester has a melting point of 50° C. or more and 80° C. or less, and is preferably at least one selected from the group consisting of glycerin fatty acid esters and higher alcohol fatty acid esters, from the viewpoint of ease of dispersion during kneading. Examples of glycerin fatty acid esters include glycerin monostearate, glycerin monobehenate, glycerin monooleate, glycerin monolaurate, stearin distearate, glycerin dibehenate, and glycerin dioleate. Examples of higher alcohol fatty acid esters include stearyl stearate, lauryl stearate, lauryl laurate, and stearyl behenate. The amount of the fatty acid ester is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the fatty acid ester is preferably 1 part by mass or more, more preferably 3.0 parts by mass or more, and even more preferably 5.0 parts by mass or more, from the viewpoint of uniformly dispersing the metal hydroxide and EVA without aggregation and ensuring uniform adhesion of the rubber foam 1 to the pressure-sensitive adhesive layer 3. On the other hand, the fatty acid ester is preferably 10.0 parts by mass or less, more preferably 8.0 parts by mass or less, and even more preferably 7.0 parts by mass or less, from the viewpoint of suppressing adhesion inhibition due to oil bleeding and ensuring adhesion of the rubber foam 1 to the pressure-sensitive adhesive layer 3. From these viewpoints, the amount of the fatty acid ester is preferably 1.0 parts by mass or more and 10.0 parts by mass or less, more preferably 3.0 parts by mass or more and 8.0 parts by mass or less, and even more preferably 5.0 parts by mass or more and 7.0 parts by mass or less.

[0026] (2.8) Nitrogen-based flame retardants The nitrogen-based flame retardant is not particularly limited. Examples of the nitrogen-based flame retardant include melamine-based flame retardants, triazine compounds, and guanidine compounds. Examples of the melamine-based flame retardant include melamine and melamine cyanurate. As the nitrogen-based flame retardant, melamine cyanurate is preferred. Melamine cyanurate has the property of not impairing the processability of the rubber compound even when highly filled. The nitrogen-based flame retardants may be used alone or in combination of two or more kinds. The amount of the nitrogen-based flame retardant is not particularly limited. When the total amount of EPDM and EVA is 100 parts by mass, the nitrogen-based flame retardant is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, and even more preferably 65 parts by mass or more from the viewpoint of ensuring high flame retardancy. On the other hand, the nitrogen-based flame retardant is preferably 150 parts by mass or less, more preferably 110 parts by mass or less, and even more preferably 90 parts by mass or less from the viewpoint of kneading processability and molding processability. In detail, the nitrogen-based flame retardant does not have reinforcing properties for rubber like carbon black, so that the durability and strength are reduced by adding a large amount, and therefore 150 parts by mass or less is preferable. In addition, when the viscosity of the composition increases, the foaming property is controlled and low density cannot be ensured, so 150 parts by mass or less is preferable. From these viewpoints, the amount of the nitrogen-based flame retardant is preferably 50 parts by mass or more and 150 parts by mass or less, more preferably 60 parts by mass or more and 110 parts by mass or less, and even more preferably 65 parts by mass or more and 90 parts by mass or less.

[0027] (2.9) Phosphorus-based flame retardants The composition may further contain a phosphorus-based flame retardant. By using a nitrogen-based flame retardant alone, a test piece having a thickness of 10 mm or more in a vertical combustion test can pass V0, but in order to pass V0 with a test piece having a thickness of less than 10 mm (e.g., 3 mm), it is preferable to use a nitrogen-based flame retardant and a phosphorus-based flame retardant in combination. The phosphorus-based flame retardants may be used alone or in combination of two or more. The phosphorus-based flame retardant is not particularly limited as long as it contains phosphorus atoms in the molecule. Examples of the phosphorus-based flame retardant include red phosphorus-based flame retardants (flame retardants containing red phosphorus) and organic phosphorus compounds. Known red phosphorus-based flame retardants can be used. Red phosphorus has attracted attention in recent years due to its flame retardancy, low smoke generation, and low toxic gas properties. Red phosphorus generally promotes carbonization of the matrix and forms a surface carbonized layer, thereby blocking oxygen and providing flame retardancy. Furthermore, a mechanism has been proposed in which phosphorus becomes polyphosphoric acid through methanoic acid, and in this process a protective coating is formed, blocking oxygen and providing flame retardancy. It is believed that the flame retardant effect of red phosphorus is expressed by the combination of carbonization promotion and coating effect. For example, Hishiguard CP (manufactured by Nippon Kagaku Co., Ltd.), which is surface-treated with aluminum hydroxide or the like to have an average particle size of about 15 μm, and 1140T (manufactured by Rinkagaku Kogyo Co., Ltd.) can be used as red phosphorus. In addition, in consideration of dispersibility in rubber, master batch type (EVA, etc.) can also be used as red phosphorus. Examples of the organic phosphorus compound include melamine polyphosphate, ammonium polyphosphate, phosphazene compounds, melamine pyrophosphate, phosphoric acid, melamine orthophosphate, melamine phosphate, piperazine orthophosphate, piperazine pyrophosphate, and piperazine polyphosphate. The phosphazene compound is preferably a cyclic phenoxyphosphazene represented by the following general formula. Examples of the organic phosphorus compound that can be used include ADK STAB EP-2500 and BUDIT667 (Budenheim), and the phosphazene that can be used is Rabitle FP-100 (Fushimi Pharmaceutical).

[0028] [ka] (wherein n represents an integer of 3 to 25.)

[0029] The amount of the phosphorus-based flame retardant is not particularly limited. When the total of EPDM and EVA is 100 parts by mass, the phosphorus-based flame retardant is preferably more than 0 parts by mass, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, from the viewpoint of ensuring higher flame retardancy in a vertical combustion test. On the other hand, the phosphorus-based flame retardant is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and even more preferably 17 parts by mass or less, from the viewpoint of suppressing the increase in viscosity of the compound (kneaded product) and controlling the foaming property to obtain a low-density rubber foam. From these viewpoints, the amount of the phosphorus-based flame retardant is preferably more than 0 parts by mass and 20 parts by mass or less, more preferably 3 parts by mass or more and 18 parts by mass or less, and even more preferably 5 parts by mass or more and 17 parts by mass or less. In addition, non-halogen flame retardants such as nitrogen-based flame retardants and phosphorus-based flame retardants have a high flame retardant effect, but they do not provide as high an effect as halogen-based flame retardants, so it is preferable to use a combination of multiple types.

[0030] (2.10) Other ingredients The composition may contain additives such as crosslinking accelerators (vulcanization accelerators), urea foaming assistants, fillers, softeners, flame retardants, glass fibers, wood flour, fibers, dehydrating agents, antioxidants, antioxidants, various micro- and nano-capsules, pigments, colorants, anti-mold agents, reinforcing materials (various carbon blacks), and expandable graphite, in addition to the above-mentioned EPDM, EVA, foaming agents, crosslinking agents, paraffin-based oils, metal hydroxides, fatty acid esters, nitrogen-based flame retardants, and phosphorus-based flame retardants. The additives may be used alone or in combination of two or more.

[0031] (2.10.1) Crosslinking accelerators (vulcanization accelerators) Examples of the crosslinking accelerator include zinc oxide (zinc oxide lubricant), thiazoles (e.g., 2-mercaptobenzothiazole, dibenzothiazyl disulfide, etc.), dithiocarbamic acids (e.g., sodium dimethyldithiocarbamate, sodium diethyldithiocarbamate, zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, etc.), guanidines (e.g., diphenylguanidine, di-o-tolylguanidine, etc.), sulfenamides (e.g., benzothiazyl-2-diethylsulfenamide, N-cyclohexyl-2-benzothiazylsulfene, etc.), and the like. Amides, thiurams (e.g., tetramethylthiuram monosulfide, tetramethylthiuram disulfide, etc.), xanthogenic acids (e.g., sodium isopropyl xanthogenate, zinc isopropyl xanthogenate, etc.), aldehyde ammonias (e.g., acetaldehyde ammonia, hexamenthylenetetramine, etc.), aldehyde amines (e.g., n-butylaldehyde aniline, butylaldehyde monobutylamine, etc.), thioureas (e.g., diethylthiourea, trimethylthiourea, etc.), dithiophosphide crosslinking accelerators, etc. are used. One of these crosslinking accelerators may be used alone, or two or more of them may be used in combination. From the viewpoint of timing adjustment of the foaming rate and the vulcanization rate, zinc oxide, thiazoles, thioureas, dithiocarbamic acids, and sulfenamides are preferably used. In addition, from the viewpoints of bloom resistance, durability, foam moldability, crosslinking speed adjustment, and the like, the mixing ratio of the crosslinking accelerator is, for example, preferably 0.5 parts by mass or more and 10.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 5.0 parts by mass or less, per 100 parts by mass of the total of EPDM and EVA.

[0032] (2.10.2) Urea-based foaming aids The urea-based foaming assistant is composed mainly of urea, and examples thereof include Cellpaste K-5 and Cellpaste 101 manufactured by Eiwa Chemical Industry Co., Ltd. The term "main component" refers to a substance whose content (mass%) is 90 mass% or more (100 mass% or less). The mixing ratio of the urea-based foaming aid is preferably 0.5 parts by mass or more and 2.0 parts by mass or less, and more preferably 0.7 parts by mass or more and 1.3 parts by mass or less, per 100 parts by mass of the total of EPDM and EVA, from the viewpoint of adjusting the decomposition initiation temperature of the foaming agent during foam molding.

[0033] (2.10.3) Fillers The filler is not particularly limited, but examples thereof include inorganic fillers such as calcium carbonate (heavy calcium carbonate, etc.), magnesium carbonate, silicic acid and its salts, clay, talc, mica powder, bentonite, silica, alumina, aluminum silicate, acetylene black, furnace black, and aluminum powder, organic fillers such as cork, and other known fillers. These fillers may be used alone or in combination of two or more. Calcium carbonate, clay, and silica are preferably used. The blending ratio of the filler is not particularly limited, but is preferably 30 parts by mass or more and 200 parts by mass or less, and more preferably 50 parts by mass or more and 900 parts by mass or less, per 100 parts by mass of the total of EPDM and EVA.

[0034] (2.10.4) Softeners The softener is not particularly limited. In the present disclosure, for example, known softeners such as plasticizers, liquid paraffin, rosin, chroman resin, polybutene, asphalt, etc. can be used. These softeners may be used alone or in combination of two or more. Preferably, petroleum oils and asphalts are used. From the standpoint of ensuring flexibility, kneading processability, and adhesion of the pressure-sensitive adhesive, the blending ratio of the softener is, for example, preferably 0 parts by mass or more and 100 parts by mass or less, and more preferably 5 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of the total of EPDM and EVA.

[0035] (2.11) Adhesion mechanism between rubber foam 1 and adhesive layer 3 The adhesion mechanism between rubber foam 1 and pressure-sensitive adhesive layer 3 is not clear, but is presumed to be as follows. However, the present disclosure should not be construed as being limited in any way by this presumed mechanism. First, a case where the rubber foam 1 does not contain fatty acid ester (RCOOR') will be described. In this case, since EVA is prone to self-aggregation, it is considered that the metal hydroxide is present in the rubber foam 1 so as to surround the EVA. Then, it is presumed that only the hydroxyl group of the metal hydroxide facing the pressure-sensitive adhesive layer 3 side among the metal hydroxides in the aggregated state of EVA forms a hydrogen bond with a polar group such as a carboxyl group of the resin contained in the pressure-sensitive adhesive layer 3, thereby adhering the rubber foam 1 and the pressure-sensitive adhesive layer 3. In this embodiment, only a small part of the metal hydroxide in the aggregated state is involved in adhesion. Also, in this embodiment, since EVA is surrounded by the metal hydroxide, it is hardly involved in adhesion. Therefore, it is presumed that when the rubber foam 1 does not contain fatty acid ester, the adhesion between the rubber foam 1 and the pressure-sensitive adhesive layer 3 is low and the adhesive force is weak. Next, a case where the rubber foam 1 contains a fatty acid ester (RCOOR') will be described. In this case, the hydrophilic site (C=O) of the fatty acid ester forms a hydrogen bond with the hydroxyl group (-OH) of the metal hydroxide. On the other hand, the hydrophobic site (-R, -OR') of the fatty acid ester has a high affinity with the hydrophobic segment of EVA. Such a fatty acid ester having a hydrophilic site and a hydrophobic site is considered to act as a dispersant for the metal hydroxide. It is presumed that this action keeps the EVA in a dispersed state without self-aggregation. It is presumed that the metal hydroxide does not aggregate around the EVA in the rubber foam 1. In this way, since the metal hydroxide does not aggregate, it is presumed that more metal hydroxide molecules are involved in the adhesion between the rubber foam 1 and the pressure-sensitive adhesive layer 3 than in the case of aggregation. Also, in this embodiment, since the EVA is not surrounded by the metal hydroxide, the EVA itself also participates in the adhesion. Therefore, when the rubber foam 1 contains a fatty acid ester, it is presumed that the adhesion between the rubber foam 1 and the pressure-sensitive adhesive layer 3 is high and the adhesive force is strong. When the adhesive layer 3 is formed by pressure laminating an adhesive to the rubber foam 1 with a roll, the EVA itself is thought to contribute to adhesion as follows: Due to the action of the fatty acid ester, the EVA is dispersed almost uniformly in the rubber foam 1. An adhesive (such as an acrylic adhesive containing an acrylic polymer) is pressure-welded to this rubber foam 1 while applying heat (e.g., 70°C to 80°C) with a roll. Then, the EVA near the surface of the rubber foam 1 is thermally melted, and it is presumed that this EVA itself contributes to pressure adhesion.

[0036] (2.12) Estimated mechanism by which rubber foam 1 has flame retardancy conforming to the 94V-0 standard specified in UL-94 Rubber foam 1 of the present disclosure is obtained by blending EPDM with EVA and a metal hydroxide, and has good adhesion to pressure-sensitive adhesive layer 3 and excellent flame retardancy. The reason why rubber foam 1 of the present disclosure has excellent flame retardancy is presumed to be as follows. Metal hydroxides are self-extinguishing and flame retardant due to their dehydrating action. EVA also has a relatively high oxidation index among olefin resins. Therefore, EVA also contributes to flame retardancy. As explained above in the section (2.11), in the rubber foam 1 of the present disclosure, the EVA and metal hydroxide are well dispersed due to the action of the fatty acid ester, which is believed to increase the adhesion between the rubber foam 1 and the pressure-sensitive adhesive layer 3 and also to allow the EVA and metal hydroxide to effectively contribute to flame retardancy. Rubber foam 1 of the present disclosure further contains a nitrogen-based flame retardant, and therefore high flame retardancy is ensured even when highly foamed (low density).

[0037] 2.Laminate 5 (1) Configuration of Laminate 5 The laminate 5 is formed by laminating a pressure-sensitive adhesive layer 3 onto a rubber foam 1 (see FIG. 1). The pressure-sensitive adhesive layer 3 contains an acrylic polymer. An acrylic polymer is a polymer obtained by polymerizing (for example, solution polymerization, emulsion polymerization, or UV polymerization) an alkyl (meth)acrylate monomer using a polymerization initiator. In other words, an acrylic polymer is a compound (resin) having a structural unit derived from an alkyl (meth)acrylate. Here, "(meth)acrylic" means acrylic or methacrylic. The acrylic polymer may contain a monomer other than the (meth)acrylic acid alkyl ester. The acrylic polymer may have a crosslinked structure formed by a crosslinking agent.

[0038] The number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester is not particularly limited. The number of carbon atoms in the alkyl group is preferably 1 to 20. The alkyl group may be either linear or branched. Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, normal butyl (meth)acrylate, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, normal octyl (meth)acrylate, isononyl (meth)acrylate, and lauryl (meth)acrylate, etc. The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.

[0039] In 100% by mass of the acrylic polymer, the constituent units derived from a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 20 carbon atoms are preferably 50% by mass or more, and more preferably 70% by mass or more. The constituent units derived from a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 20 carbon atoms may be 100% by mass.

[0040] The acrylic polymer may also contain structural units derived from other monomers than the (meth)acrylic acid alkyl ester. The other monomers are not limited. Known monomers may be used.

[0041] In the polymerization of the (meth)acrylic acid alkyl ester, an acrylic polymer can be easily formed by utilizing a polymerization reaction caused by heat or ultraviolet light using a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator. The polymerization initiator can be used alone or in combination of two or more kinds. Examples of the thermal polymerization initiator include an azo-based polymerization initiator, a peroxide-based polymerization initiator, and a redox-based polymerization initiator. The amount of the polymerization initiator used is not particularly limited. The amount of the polymerization initiator used is appropriately adjusted, for example, as follows. That is, when the adhesive layer 3 is formed by applying the adhesive with a roll coater or the like, the amount used is adjusted before application so as not to cause polymerization.

[0042] The pressure-sensitive adhesive layer 3 can contain various known compounding agents (additives) such as compounds for improving adhesion to the rubber foam 1. Examples of compounding agents that can be used include metal particles, metal oxides, carbide particles, ceramic particles, calcium carbide, aluminum hydroxide, glass, silica, various resin beads, nylon resins, organic / inorganic hollow bodies, hollow glass balloons, etc. Examples of metal particles include particles of copper, nickel, aluminum, chromium, iron, stainless steel, and the like. Examples of the carbide particles include silicon carbide and nitrogen carbide. Ceramic particles include particles of nitrides, glasses, alumina, zirconium, etc., oxides, etc. The compounding agents may be contained alone or in combination of two or more.

[0043] The thickness of the rubber foam 1 in the laminate 5 is not particularly limited and can be changed appropriately depending on the application. The thickness of the rubber foam 1 is, for example, 0.1 mm or more and 2.0 mm or less. The thickness of the pressure-sensitive adhesive layer 3 in the laminate 5 is not particularly limited and can be appropriately changed depending on the application. The thickness of the pressure-sensitive adhesive layer 3 is preferably 0.2 mm or more and 1.0 mm or less, and more preferably 0.3 mm or more and 0.8 mm or less.

[0044] The peel strength between the pressure-sensitive adhesive layer 3 and the rubber foam 1 in the laminate 5 is preferably 5 N / 25 mm or more. The upper limit of the peel strength is not particularly limited, but is usually 50 N / 25 mm or less. The peel strength is a peel strength (N / 25 mm) measured in accordance with a method based on JIS K 0237 (90° peel test method), as described below.

[0045] (2) Method for manufacturing laminate 5 The method for producing the laminate 5 is not particularly limited. The laminate 5 is produced, for example, as follows. For example, an acrylic adhesive mixture (containing a thermal polymerization initiator and a filler) is coated on a release paper using a roll coater or the like, and then thermally cured in a hot air tank to form an adhesive layer 3. Thereafter, a rubber foam 1 is pressure-bonded onto the adhesive layer 3 using a roll, and the resulting mixture is allowed to cool, thereby producing a laminate 5. For coating, in addition to a roll coater, a coating roll such as a comma coater, a slot die, etc. can also be suitably used. In particular, when the pressure-sensitive adhesive layer 3 is formed on both sides (the front and back sides) of the rubber foam 1, or when the pressure-sensitive adhesive layer 3 has a multi-layer structure, the multi-layer slot die is suitably used. In addition, a release liner may be attached to the adhesive surface of the adhesive layer 3 as a liner. EXAMPLES

[0046] The present invention will be described more specifically below with reference to examples.

[0047] 1. Preparation of Rubber Foam (Examples 1-15 and Comparative Examples 1-4) Various rubber foams were produced according to the compounding ratios shown in Table 1-3. Details of the main raw materials in Table 1-3 are shown below. EPDM: Mitsui EPT4021 manufactured by Mitsui Chemicals, Inc. was used. EVA: Novatec LV440 (ethylene / ethyl acetate = 85 wt% (mass%) / 15 wt% (mass%), melting point 89°C) manufactured by Japan Polyethylene Co., Ltd. was used. Fatty acid esters: As the fatty acid ester (1), Rikemal SL-800 (stearyl stearate) manufactured by Riken Vitamin Co., Ltd. was used. As the fatty acid ester (2), Rikemal S-100 (glycerin monostearate) manufactured by Riken Vitamin Co., Ltd. was used. Paraffin-based process oil (abbreviated as "paraffin-based oil" in the table): Diana Process PS-430 manufactured by Idemitsu Kosan Co., Ltd. was used. Vulcanization accelerator: As an inorganic vulcanization accelerator, zinc oxide (Inoue Sekiryo Kogyo Co., Ltd., zinc oxide type 2 (5 parts by mass)) was used. As a thiazole-based vulcanization accelerator, Noccela M (0.7 parts by mass) manufactured by Ouchi Shinko Chemical Co., Ltd. was used. As a thiuram-based vulcanization accelerator, Noccela TT (1.4 parts by mass) manufactured by Ouchi Shinko Chemical Co., Ltd. was used. Crosslinking agent (vulcanizing agent): Sulfur (Rhenogran S-80E, manufactured by Lanxess AG, 2.5 parts by mass) was used. Foaming assistant: A urea-based foaming assistant (Cell Paste K-5, manufactured by Eiwa Chemical Industry Co., Ltd., 4.6 parts by mass) was used. Foaming agent: Azodicarbonamide (Vinifoll AC#3W, manufactured by Eiwa Chemical Industry Co., Ltd., 15 parts by mass) was used. ·Metal hydroxide: The aluminum hydroxide used was C-301N (manufactured by Sumika Alchem ​​Co., Ltd.). The magnesium hydroxide used was Kisuma 5A (Kyowa Chemical Industry Co., Ltd.). Carbon black: Asahi Carbon #50G (20 parts by mass) manufactured by Asahi Carbon Co., Ltd. was used. Nitrogen-based flame retardants: As the nitrogen-based flame retardant (1), melamine cyanurate MC-4500 (manufactured by Nissan Chemical Industries, Ltd.) was used. As the nitrogen-based flame retardant (2), melamine (manufactured by Nissan Chemical Industries, Ltd.) was used. Phosphorus-based flame retardants: As the phosphorus-based flame retardant (1), a red phosphorus-based flame retardant (special surface treatment coated red phosphorus 1140T, manufactured by Rin Chemical Industry Co., Ltd.) was used. As the phosphorus-based flame retardant (2), Adeka STAB FP-2500 (melamine polyphosphate, manufactured by Adeka Corporation) was used. As the phosphorus-based flame retardant (3), BUDIT667 (ammonium polyphosphate complex, manufactured by Budenheim) was used. As the phosphorus-based flame retardant (4), Rabitle FP-100 (phenoxyphosphazene oligomer, manufactured by Fushimi Pharmaceutical Co., Ltd.) was used.

[0048] Specifically, each rubber foam was produced as follows. <Example 1-15> EPDM, EVA, carbon black, paraffin-based process oil, flame retardant, zinc oxide, fatty acid ester, and metal hydroxide were all charged into a Banbury mixer at once, and the compound was discharged when it reached 130°C. Next, sulfur, azodicarbonamide, urea-based foaming assistant, thiazole-based vulcanization accelerator, and thiuram-based vulcanization accelerator were added to the compound, which was then kneaded with a mixing roll and extruded into a sheet. The sheet was set in a mold at 130° C. and subjected to primary press molding for 15 minutes, and then secondary press molding was performed at 160° C. for 15 minutes to crosslink and foam the sheet, thereby obtaining a rubber foam.

[0049] <Comparative Example 1> A rubber foam was produced in the same manner as in Example 1-15, except that EVA was not used. <Comparative Example 2> A rubber foam was produced in the same manner as in Examples 1 to 15, except that no metal hydroxide was used and no flame retardant was used. In Comparative Example 2, no nitrogen-based flame retardant was used. <Comparative Example 3> A rubber foam was produced in the same manner as in Examples 1 to 15, except that no metal hydroxide was used. In Comparative Example 3, no nitrogen-based flame retardant was used. <Comparative Example 4> A rubber foam was produced in the same manner as in Example 1-15, except that no metal hydroxide was used and expandable graphite was used.

[0050] Each rubber foam (Examples 1-15, Comparative Examples 1-4) is considered to have a closed cell structure because the water absorption rate is low at 1 to 12%. Rubber foams with a closed cell structure generally have high water stop performance but poor adhesion (adhesiveness) to a pressure-sensitive adhesive layer. On the other hand, rubber foams with an open cell structure (water absorption rate of 100 to 300%) generally have low water stop performance but high adhesion (adhesiveness) to a pressure-sensitive adhesive layer.

[0051] 2. Preparation of Laminates (Examples 1-15, Comparative Examples 1-4) The acrylic copolymer used was SK Dyne 1717DT, an ethyl acetate-containing adhesive manufactured by Soken Chemical Industries, Ltd. The crosslinking agent used was E-AX (manufactured by Soken Chemical Industries, Ltd.) The raw material composition for the adhesive layer was prepared by blending 0.05 parts by mass of a crosslinking agent with 100 parts by mass of this polymer, adding 10 parts by mass of an acrylic monomer (4-hydroxybutyrate; manufactured by Osaka Organic Chemical Industry Co., Ltd.: 4HBA) and 0.02 parts by mass of t-butylperoxy-2-ethylhexarate (manufactured by NOF Corp., Perbutyl O) as a thermal polymerization initiator. The raw material composition was coated on a release paper using a roll coater, and then heat cured in a hot air tank (90°C, 10 minutes) to form an adhesive layer. Then, a rubber foam was pressed onto the adhesive layer using a roll, and the adhesive layer was cooled to produce a laminate. The adhesive layer in the laminate had a thickness of 0.3 mm.

[0052] 3. Evaluation method (1) Apparent density The apparent density was measured in accordance with JIS-K 6767.

[0053] (2) 50% compression load The compression load of the rubber foam was measured in accordance with JIS-K 6767. The skin layer of the rubber foam was removed to prepare a test piece with a thickness of 10 mm. Then, using a compression tester, the test piece was compressed by 50% at a compression speed of 10 mm / min, and the compression load after 10 seconds was measured.

[0054] (3) Measurement of water absorption rate The water absorption rate of the rubber foam was measured in accordance with ASTM D 1056. The skin layer of the rubber foam was removed to prepare a test piece having a thickness of 12.5 mm and a size of 50 mm×50 mm. After measuring the weight of the test piece, the test piece was immersed 50 mm below the water surface, placed under a reduced pressure of 17 kPa for 3 minutes, and then immersed at atmospheric pressure for 3 minutes. After immersion, the water droplets on the surface were wiped off, the weight of the test piece after immersion was measured, and the water absorption rate was calculated using the following formula.

[0055]

number

[0056] (4) Measurement method for 90 degree peel strength A test piece measuring 25 mm x 250 mm was cut from the rubber foam laminated with the adhesive, and a 25 mm x 125 mm portion of the adhesive surface was pressed onto a stainless steel plate. Thereafter, using a tensile tester, the test piece was peeled off from the stainless steel plate in a direction of 90 degrees at a peeling speed of 300 mm / min, and the 90 degree peel strength was measured. The 90 degree peel strength is a peel strength (N / 25 mm) measured in accordance with a method based on JIS K 0237 (90 degree peel test method).

[0057] (5) UL94 vertical flame test Rubber foams of each thickness were tested according to the vertical burning test based on the UL94 standard. Burning times of 50 seconds or less were rated as V0 pass based on the V0 standard. Burning times of 250 seconds or less were rated as V1 pass based on the V1 standard.

[0058] [Table 1]

[0059] [Table 2]

[0060] [Table 3]

[0061] 4.Results The results are shown in Tables 1-3. In Table 1-3, the columns for the condition of the rubber foam (molded product) are A, B, C, and D as follows: <State of rubber foam> A: No warping, pinholes or cracks in the rubber foam. Good condition. B: The rubber foam is slightly warped and cracked. No pinholes. C: The rubber foam has a little more warping, cracks, and pinholes. D: The rubber foam has a lot of warping, cracks, and pinholes. There is a lot of air entrapment.

[0062] In Table 1-3, the A, B, C, and D in the overall judgment column have the following meanings: A: The adhesive layer has good adhesion, and the rubber foam is in good condition. B: The adhesive layer has good adhesion, but the rubber foam has some warping and cracking. C: The adhesive layer has slightly poor adhesion, and the rubber foam has some warping and cracking. D: The adhesive layer has poor adhesion. The rubber foam has a lot of warping, cracking, and pinfall.

[0063] (1) Fulfillment of each requirement in Examples 1-15 The compositions constituting the rubber foams of Examples 1 to 15 satisfy all of the following requirements (a) to (f). · Requirement (a): Contains EPDM. · Requirement (b): Contains EVA. · Requirement (c): Contains paraffinic processing oil. · Requirement (d): Contains a metal hydroxide. · Requirement (e): Contains fatty acid esters. · Requirement (f): Contains nitrogen-based flame retardants.

[0064] (2) Fulfillment of each requirement in Comparative Examples 1-4 In contrast, the rubber foam of Comparative Example 1-4 does not satisfy the following requirements. Comparative Example 1 does not satisfy the requirement (b). Comparative Example 2 does not satisfy the requirements (d) and (f). Comparative Example 3 does not satisfy the requirements (d) and (f). Comparative Example 4 does not satisfy the requirement (d).

[0065] (3) Results and Discussion The rubber foam of Example 1-15 was in good condition and was also judged to be good overall. That is, it was confirmed that the rubber foam of Example 1-15 had good moldability and high adhesion to the acrylic pressure-sensitive adhesive. Furthermore, the rubber foam of Example 1-15 had a short burning time in the vertical burning test based on the UL94 standard and had high flame retardancy. Furthermore, the rubber foam of Example 1-15 had a low apparent density (0.08 g / cm 3 ~0.25g / cm 3 ) and has a closed cell structure (water absorption rate of 4% or less), which provides good water-stopping properties. Furthermore, the laminates produced from the rubber foams of Examples 1-15 had sufficient adhesion between the rubber foam and the pressure-sensitive adhesive layer, and were therefore suitable for practical use. In contrast, Comparative Example 1, which did not contain EVA, was inferior to the Examples in the state of the rubber foam, the 90-degree peel strength, and the results of the vertical flame test, and was also inferior to the Examples in the overall evaluation. Furthermore, in Comparative Example 2, which did not contain a metal hydroxide or a nitrogen-based flame retardant, the results of the 90 degree peel strength and the vertical combustion test were inferior to those of the Examples, and the overall evaluation was also inferior to that of the Examples. Moreover, in Comparative Example 3, which did not contain a metal hydroxide or a nitrogen-based flame retardant, the state of the rubber foam and the 90 degree peel strength were inferior to those of the Examples, and the overall evaluation was also inferior to that of the Examples. Moreover, in Comparative Example 4, which did not contain a metal hydroxide, the state of the rubber foam and the 90 degree peel strength were inferior to those of the Examples, and the overall evaluation was also inferior to that of the Examples. Next, Example 2, in which a nitrogen-based flame retardant was used alone, and Examples 8, 9, 10, 11, and 12, in which a nitrogen-based flame retardant and a phosphorus-based flame retardant were used in combination, are compared. Example 2 passed V0 for test pieces with a thickness of 10 mm and 5 mm, but passed V1 for test pieces with a thickness of less than 5 mm (3 mm and 1 mm). Examples 8, 9, 10, 11, and 12 passed V0 for test pieces with a thickness of 10 mm and 5 mm, and also passed V0 for test pieces with a thickness of less than 5 mm (3 mm and 1 mm). From these results, it was confirmed that higher flame retardancy can be ensured by using a nitrogen-based flame retardant and a phosphorus-based flame retardant in combination.

[0066] 5. Effects of the embodiment According to the above examples, a rubber foam having high flame retardancy, low density, and high adhesion to an acrylic resin-containing pressure-sensitive adhesive layer can be provided without using a halogen-based flame retardant. Also, according to the examples, a laminate having high flame retardancy, low density, and high adhesion between the rubber foam and the pressure-sensitive adhesive layer can be provided without using a halogen-based flame retardant.

[0067] The present disclosure is not limited to the above-described embodiments, and various modifications and variations are possible. [Explanation of symbols]

[0068] 1...Rubber foam 3...Adhesive layer 5...Laminate

Claims

1. A foam of a composition containing EPDM, EVA, a foaming agent, a crosslinking agent, a metal hydroxide, a fatty acid ester, and a nitrogen-based flame retardant, The composition includes a process oil, the amount of the process oil is 3 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the total of the EPDM and the EVA.

2. The rubber foam according to claim 1 , wherein the composition further comprises a phosphorus-based flame retardant.

3. The water absorption rate measured according to ASTM D 1056 is 0% or more and 30% or less, The rubber foam according to claim 1 or 2, which has a closed cell structure.

4. A laminate comprising the rubber foam according to claim 1 and a pressure-sensitive adhesive layer laminated thereon.

5. The laminate according to claim 4 , wherein the pressure-sensitive adhesive layer contains an acrylic polymer.

Citation Information

Patent Citations

  • Flame-retardant epdm foam

    JP2002293976A

  • Rubber foam

    JP2003041038A

  • Rubber foam and its production method

    JP2009074014A

  • EPDM foam and adhesive sealing material

    JP2012017452A

  • Foam laminate

    JP2014180818A